Structural-capacity-reserve-based performance assessment of long-span single-layer lattice shell structures. (August 2019) - He, Zheng; Liu, Tingting
Abstract: To achieve a well-balanced structural design, a customized performance assessment approach based on the structural capacity reserve (SCR) is proposed for commonly used long-span single-layer lattice shells. The SCR is calculated by integrating the normalized residual seismic capacity (RSC) over the entire range of possible earthquake-induced damage levels. Six typical RSC ratio curves and the corresponding ranges of the SCR index are discussed and verified for several spherical single-layer lattice shells. The impact of the arrangement of the components on the structural deformability, failure mode, plasticity and damage development as well as the RSC and SCR is clarified for two Schwedler shells. Based on observations from vulnerability and sensitivity analyses, several alternative strengthening schemes are generated for an S12 Schwedler single-layer lattice shell, and the optimal one is determined by means of a multiple-objective evaluation system that includes the SCR. The investigation indicates that normalized RSC ratio curves can reflect the design rationality of structural layouts and that they can clearly capture the dynamic instability of lattice shells. The ability of lattice shells to retain their post-earthquake resistance reserves is found to depend primarily on the locations where damage develops. The localization of fully yielded components has the potential to create several weak regions, leading to a high possibility of substantial loss of resistance reserves. The case study of the S12 Schwedler shell demonstrates the necessity of considering the SCR in a comprehensive structural performance evaluation system. Highlights: Detailed clarification about the correlation between structural RSC and its related quantities. SCR reflects the design rationality of lattice shells with various structural layouts. An efficient multi-objective seismic performance evaluation system with SCR is developed. The characteristics of SCR are addressed and demonstrated by some lattice shells.